2008
DOI: 10.1021/ja8047046
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Magnetic Switching and Linkage Isomerism in K0.4Fe4[Cr(CN)6]2.8·16H2O: X-ray Absorption and Magnetic Circular Dichroism Studies

Abstract: Abstract:The effect of applied pressure on the magnetic properties of the Prussian blue analogue K 0.4Fe4[Cr(CN)6]2.8 · 16H2O (1) has been analyzed by dc and ac magnetic susceptibility measurements. Under ambient conditions, 1 orders ferromagnetically at a critical temperature (T C) of 18.5 K. Under application of pressure in the 0-1200 MPa range, the magnetization of the material decreases and its critical temperature shifts to lower temperatures, reaching T C ) 7.5 K at 1200 MPa. Pressure-dependent Raman and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 73 publications
6
108
0
Order By: Relevance
“…The Mn L 2,3 -edge XAS spectra of all the samples were nearly the same, which suggested that the electronic structure of Mn remains unchanged during Li-ion insertion/extraction. To analyze the spectra in detail, we also performed CTM calculations [12][13][14][15][16] . The calculated spectrum is also shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The Mn L 2,3 -edge XAS spectra of all the samples were nearly the same, which suggested that the electronic structure of Mn remains unchanged during Li-ion insertion/extraction. To analyze the spectra in detail, we also performed CTM calculations [12][13][14][15][16] . The calculated spectrum is also shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Various magnetic properties of Prussian blue analogues (PBAs), such as photomagnetism, [11] room-temperature ferrimagnetism, [12] spin crossover [13] and so on, [14] have been reported in the last two decades. Solid-state electrochemical techniques are useful for modulating their magnetic properties.…”
Section: àmentioning
confidence: 99%
“…[1,2] Small external perturbations, for instance magnetic field, pressure, or light, can change important energy and length scales, driving these flexible materials into new areas of phase space with very different properties. [3][4][5][6][7][8][9] These competing states are interesting and useful because of their different functionalities. Finite length scale effects also influence the interaction between charge, structure, and magnetism.…”
Section: Introductionmentioning
confidence: 99%